2024
DOI: 10.1021/acs.inorgchem.3c04230
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Carbaporphyrins: Oxygenation Reactivities Dependent upon Coordinating Structures

Fangling Deng,
Xinrun Ge,
Zhongyu Deng
et al.

Abstract: Cu II metalations of carbaporphyrins 1−4 gave the corresponding Cu II complexes 1-Cu, 2-Cu, 3-Cu, and 4-Cu with varying degrees of distortions in Cu II square-planar coordination. Upon treatment with Cu(OAc) 2 , 1-Cu was inert but 2-Cu and 3-Cu gave the respective O-atom-inserted complexes 2-OCu and 3-OCu. Further, 3-Cu and 4-Cu were converted to mesomethoxynickel(II) porphyrins 3-OMe and 4-OMe, respectively, via treatment with Cu(OAc) 2 in methanol. meso-Hydroxynickel(II) porphyrin 3-OH was obtained by the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Further, 2-OCu was converted to meso -oxygenated products, such as 2-OMe or 2-OH (Scheme ). These results indicate that the oxidative functionalization of C–H bond has been accomplished in an indirect manner. It may also be suggested that earring porphyrins that will force a more distorted coordination of Cu II carbaporphyrins may be viable to enable catalytic C–H-activating functionalization.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Further, 2-OCu was converted to meso -oxygenated products, such as 2-OMe or 2-OH (Scheme ). These results indicate that the oxidative functionalization of C–H bond has been accomplished in an indirect manner. It may also be suggested that earring porphyrins that will force a more distorted coordination of Cu II carbaporphyrins may be viable to enable catalytic C–H-activating functionalization.…”
mentioning
confidence: 79%
“…In 2016, we explored earring Ni II porphyrin 1 bearing a tripyrrin strap linked at the 3,7-positions, which has a carbaporphyrins pocket and serves as an effective ligand toward transition metals to allow metalations by chelate-directed C–H bond metalation . Actually, 1 gave Pd II and Cu II complex 1-Pd and 1-Cu under suitable metalation conditions in good yields (Scheme ). Since then, various earring porphyrins have been explored. Through these studies, it has been revealed that oxygenation reactivities of Cu II carbaporphyrins become more reactive with increased distortion of the square planar Cu II coordination .…”
mentioning
confidence: 99%
See 1 more Smart Citation